Left and right vagus nerve stimulation: historical perspectives, clinical efficacy, and future directions - Sharma, Birendra; Jones, Krysten A.; Lober, Robert M.; Hatcher-Solis, Candice N. (Frontiers in Human Neuroscience, 2025)
Neuromodulation has profoundly transformed medical science, offering new treatments for various neurological conditions. Stimulation techniques that target the brain, spinal cord, trigeminal nerve, and vagus nerve (VN) use electrical impulses to modulate neural functions. Among these, vagus nerve stimulation (VNS) is distinguished for its use to stimulate the VN to modulate neural functions. VNS shows promising applications across a wide range of neurological conditions, exemplifying the ongoing evolution of neuromodulation. As VNS continues to prove its efficacy, an important consideration in its application arises over the optimal VN stimulation site due to the bilateral nature of the VN. This review highlights the need for comparative studies of left VNS (L-VNS) and right VNS (R-VNS) to enhance our understanding of neurophysiology. The advantages and limitations of stimulation to the left VN or right VN are examined to potentially lead to more personalized and effective treatment strategies.